Penanaman Nilai-nilai Ahlussunnah Wal Jama'ah pada Siswa MA Roudhotul Mujawwidin dalam Pembelajaran PAI - Ahmad Muttakin (Moral : Jurnal kajian Pendidikan Islam, 2024)
The importance of Ahlussunnah Wal Jama'ah is a teaching in Islam that follows the traditions and teachings of the Prophet Muhammad SAW, as well as the early generations of Muslims. The application of these values in PAI learning can help students understand religious teachings more authentically. Especially in the principles that exist in the teachings of Ahlussunnah Wal Jama'ah which include Tawasut, I'tidal, Tasamuh, Tawazun and Amr Ma'ruf Nahi Munkar. This study aims to determine how the application of Ahlussunnah Wal Jama'ah values and the values of Ahlussunnah Wal Jama'ah in MA Roudhotul Mujawwidin. This research uses a qualitative method with a case study approach. In collecting data, researchers used observation, interviews, and documentation. This data analysis uses triangulation of sources, time, and place. This research was conducted at Madrasah aliyah Raudhotul Mujawwidin Rimbo Bujang Jambi. The results of this study are in the application of Ahlu Sunnah Wal Jama'ah values at MA Roudlotul Mujawwidin there are 3 tasks of the teacher in realizing it. 1) Teacher as a conservator in instilling Ahlu Sunnah Wal Jama'ah values, 2) Teachers as student innovators so that students can understand the values of Ahlu Sunnah Wal Jama'ah, and 3) Teachers as transmitters are realized by teachers having a teaching mission that is sustainable. There are five values of Ahlusunnah Wal Jama'ah in PAI learning at MA Roudhotul Mujawwidin. 1) Students have a spirit of tolerance with mutual respect, 2) Students are moderate and fair in dealing with cases, 3) Students have a spirit of love for peace and harmony, 4) Students help each other, and 5) Students have a spirit of love for the country.